STUDI DESKRIPTIF TENTANG KEMAMPUAN BELAJAR MANDIRI SISWA TUNARUNGU KELAS XII DI SMK - AYU KARTIKASARI, DESY (Jurnal Pendidikan Khusus, 2016)
Abstract Self learning ability was very important to be possessed by the hearing impairment students. By self learning ability possessed by the students, it facilitated them in studying in inclusion class, the students would be able to learn actively, and not to be easy giving up in completing the task based on their own willing so that they would not depend on other people, and as the students’ provision in implementing the education forever. This research purpose was to describe (1) the students’ activeness in learning, (2) the students’ persistent in learning, (3) the students’ directedness, and (4) the students’ motive in learning. This research method was descriptive qualitative. The data was collected using the technique of observation non participant, interview, and questionnaire. The technique of observation non participant was used to obtain the data about the hearing impairment students’ activities in learning. The interview technique was used to obtain the data from the informant’s opinion i.e. class teachers about hearing impairment students during learning in the class. The questionnaire was used to obtain the data directly from the subject i.e. hearing impairment students about their activities during learning in the class. The research result indicated that two of three subjects of hearing impairment students had possessed self learning ability in either academic subject or practice. Both hearing impairment students had possessed learning activeness, they both actively asked when they had difficulty understanding the material and they also tried to participate in completing the group task or group discussion. Both subjects had also possessed persistent learning, it was seen when both subjects were given difficult enough task by the teacher they always tried to finish the task given autonomously suitable with their ability. For the learning directedness too, the students had been able to focus and determine the material which should be understood first. For the motive learning it indicated that the students had possessed motivation from themselves to learn without depending on the people around.   Keywords: ability, self learning